Risk-adjusted benchmarks in laparoscopic liver surgery in a national cohort. Issue 7 (10th January 2020) - Russolillo, N; Aldrighetti, L; Cillo, U; Guglielmi, A; Ettorre, G M; Giuliante, F; Mazzaferro, V; Dalla Valle, R; De Carlis, L; Jovine, E; Ferrero, A; Ratti, F; et al.
Abstract: Background: This study aimed to assess the best achievable outcomes in laparoscopic liver resection (LLR) after risk adjustment based on surgical technical difficulty using a national registry. Methods: LLRs registered in the Italian Group of Minimally Invasive Liver Surgery registry from November 2014 to March 2018 were considered. Benchmarks were calculated according to the Achievable Benchmark of Care (ABC™). LLRs at each centre were divided into three clusters (groups I, II and III) based on the Kawaguchi classification. ABCs for overall and major morbidity were calculated in each cluster. Multivariable analysis was used to identify independent risk factors for overall and major morbidity. Significant variables were used in further risk adjustment. Results: A total of 1752 of 2263 patients fulfilled the inclusion criteria: 1096 (62·6 per cent) in group I, 435 (24·8 per cent) in group II and 221 (12·6 per cent) in group III. The ABCs for overall morbidity (7·8, 14·2 and 26·4 per cent for grades I, II and II respectively) and major morbidity (1·4, 2·2 and 5·7 per cent) increased with the difficulty of LLR. Multivariable analysis showed an increased risk of overall morbidity associated with multiple LLRs (odds ratio (OR) 1·35), simultaneous intestinal resection (OR 3·76) and cirrhosis (OR 1·83), and an increased risk of major morbidity with intestinal resection (OR 4·61). ABCs for overall and major morbidity were 14·4 and 3·2 per cent respectively for multiple LLRs, 30 and 11·1 per cent for intestinal resection, and 14·9 and 4·8 per cent for cirrhosis. Conclusion: Overall morbidity benchmarks for LLR ranged from 7·8 to 26·4 per cent, and those for major morbidity from 1·4 to 5·7 per cent, depending on complexity. Benchmark values should be adjusted according to multiple LLRs or simultaneous intestinal resection and cirrhosis. Graphical Abstract: Data from the I Go MILS registry were used to calculate the benchmarks for outcomes in laparoscopic liver resection (LLR). Depending on the technical complexity of LLR, the benchmarks ranged between 7·8 and 26·4 per cent for overall morbidity, and 1·4 and 5·7 per cent for major morbidity. Multiple LLRs, simultaneous intestinal resection and cirrhosis worsened benchmark values. Benchmarks may be useful